Pengaruh Upacara Rumah Adat Terhadap Ketertinggalan Pendidikan Anak di Desa Oenbit - Isu, Rudolof Jibrael; Lopo, Ferdinan Leonadus (Retorika: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
This study aims to determine the effect of traditional house ceremonies on children's educational backwardness in Oenbit Village. This research is located in Oenbit Village, Insana District, North Middle East Regency. The population in this study were 295 heads of families and the sample was 32 heads of families. Sampling according to Arikunto (2010) that if the subject is less than 100, it is better to take all so that the research is a population study. Furthermore, if the subject is large, it can be taken between 10-15% or 20-25%. The data collection technique used is a questionnaire and observation technique, while the data analysis technique used in this study is simple linear regression. The results of the research on traditional house ceremonies on the backwardness of children's education in Oenbit Village. Because based on the results of the study, F table 0.05 = 3.295 < F count 0.05 = 25.909, the hypothesis Ha has a significant effect between traditional house ceremonies and children's educational backwardness. With the influence of traditional house ceremonies on the backwardness of children's education. Based on statistical calculations F count > F table. This means proving that traditional house ceremonies can have an impact on children's education.